Effect of Organic Acid Solutions on Color Change of Acrylic Resin Facing For Fixed Crowns and Bridges - Lamia T Rejab (University of Mosul, College of Dentistry, 2008)
Aim: To evaluate the effect of the organic acid solution on color stability of the facing heat-cured acrylic resin. Materials and methods: Two heat-cured facing acrylic resins were used in this study. Sixty four rectangular shape specimens were prepared to evaluate the color changes of the heat-cured acrylic resin after immersion in three organic acids (acetic, citric and lactic acids). The specimens were divided into two groups according to tested resin materials, and then subdivided into four tested groups according to immersion solution, eight specimens for each subgroup. The assessment of color property (opacity) done by using ultra-violet visible spectrophotometer at wavelength 345 nm. Mean values were compared statistically with one way analysis of variance (ANOVA) followed by Duncan , s multiple range test to determine the significant difference among the tested groups at (p<0.05) level of significance. Results: The results showed that there is a significant difference of the means value of the color change among the four tested groups for both tested materials for two different immersion periods, but there is no significant difference of color change between tested materials. Specimens immersed in acetic acid have a higher value than that immersed in other organic acids. Conclusion: The result of this study show that immersion in organic acids for different immersion periods had a significant effect on color stability of the facing heat-cured acrylic resin cured acrylic resin .